2018
DOI: 10.7326/m18-0443
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Benefits and Harms of Basal Insulin Analogues for Type 2 Diabetes

Abstract: None. (PROSPERO: CRD42016037055).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 50 publications
2
28
0
5
Order By: Relevance
“…This finding is consistent with emerging data on the comparative effectiveness and safety of different basal insulins for type 2 diabetes. 34,35 Two studies published in 2018 reported similar associations of different basal formulations with glucoselowering ability in real-world practice. 34,35 The existing literature has mainly concentrated on patients with type 2 diabetes who do not use insulin and the extent to which nonmodifiable factors are associated with diabetes control.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This finding is consistent with emerging data on the comparative effectiveness and safety of different basal insulins for type 2 diabetes. 34,35 Two studies published in 2018 reported similar associations of different basal formulations with glucoselowering ability in real-world practice. 34,35 The existing literature has mainly concentrated on patients with type 2 diabetes who do not use insulin and the extent to which nonmodifiable factors are associated with diabetes control.…”
Section: Discussionmentioning
confidence: 98%
“…34,35 Two studies published in 2018 reported similar associations of different basal formulations with glucoselowering ability in real-world practice. 34,35 The existing literature has mainly concentrated on patients with type 2 diabetes who do not use insulin and the extent to which nonmodifiable factors are associated with diabetes control. 7,8,10,36 For example, age and duration of diabetes have been elucidated as factors associated with a patient's glycemic control.…”
Section: Discussionmentioning
confidence: 98%
“…A recent systematic review and network meta-analysis found high-to-moderate evidence that detemir leads to less weight gain compared with all other basal insulins including degludec and glargine U300 and low and very low quality evidence that degludec and glargine U300 were associated with lower incidence of nocturnal hypoglycaemia than detemir and glargine U100. 25 Significantly this comprehensive meta-analysis of 39 trials including 26,195 participants with T2DM did not find significant evidence that any basal insulins were superior in terms of glycaemic effects or severe hypoglycaemic episodes. It must be noted that insulin degludec had higher rates of severe hypoglycaemia in the SWITCH 2 cross-over randomised controlled cross-over trial than insulin glargine U300 in the EDITION 2 randomised controlled trial.…”
Section: Patient Groups Most Likely To Benefitmentioning
confidence: 77%
“…10 A systematic review and network meta-analysis of thirty-nine trials comprising 26,195 patients with T2DM found low and very low quality evidence that reduced risk of nocturnal hypoglycaemia was associated with Degludec U100 and U200 and glargine 300. 25…”
Section: Hypoglycaemiamentioning
confidence: 99%
“…Four basal insulin analogues (insulin glargine 100 U/mL, insulin detemir, insulin degludec and insulin glargine 300 U/mL) have been introduced since the turn of the last century, challenging neutral protamine Hagedorn (NPH) insulin as the most widely used basal insulin, particularly in people with type 1 diabetes. Randomized trials have shown that the positive effects of these new treatment options are principally lower frequencies of hypoglycaemia and less weight gain, but the debate on the roles of these basal insulin analogues in clinical treatment guidelines remains ongoing [1][2][3].…”
Section: Introductionmentioning
confidence: 99%